Association Between Metabolic Syndrome and the Size of Renal Cysts: A Cross-Sectional Study - Tao B; Gu D; Wang K; Li Y; Xu X; Chen J (Diabetes, Metabolic Syndrome and Obesity, 2024)
Biao Tao,* Dian Gu,* Kai Wang,* Yinan Li, Xianlin Xu, Jiexun Chen Department of Urology, Sir Run Run Hospital, Nanjing Medical University, Nanjing, Jiangsu Province, 211100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiexun Chen; Xianlin Xu, Department of Urology, Sir Run Run Hospital, Nanjing Medical University, 109 Longmian Road, Jiangning District, Nanjing, Jiangsu Province, 211100, People’s Republic of China, Email cjx128619@yeah.net; xianlinxu@njmu.edu.cnBackground and Aims: Metabolic syndrome (MetS) is associated with the development of several diseases. However, the correlation between MetS and size of renal cysts remains unclear. This research aims to explore the potential connection between them, offering theoretical guidance for clinical prevention and treatment of renal cysts.Methods: A total of 467 patients diagnosed with renal cysts and admitted to Sir Run Run Hospital, Nanjing Medical University from September 2019 to September 2020 were eventually included in this study. They were divided into the small cyst group (cyst volume≤ 1.5cm³) and the large cyst group (cyst volume> 1.5cm³) based on the median value of cyst volume. Multivariate logistic regression analysis was used to evaluate the association between MetS and size of renal cysts.Results: Our results indicated that MetS (OR 1.941, 95% CI 1.286– 2.927, P=0.002) was positively associated with the size of renal cysts. Additionally, multiple renal cysts (OR 2.259, 95% CI 1.402– 3.640, P=0.001) and serum globulin (OR 0.945, 95% CI 0.905– 0.987, P=0.011) were positively and negatively related to size of renal cysts, respectively.Conclusion: Our study reveals the association between MetS and the size of renal cysts. Patients with MetS are more likely to have larger renal cysts. The administration of MetS may help limit the development of renal cysts. Further prospective studies are needed to explore the causal relationship between MetS and renal cysts.Keywords: size of renal cysts, metabolic syndrome, metabolic disease, renal cyst